IMPLEMENTATION OF ISLAM RELIGIOUS DEVELOPMENT TO INCREASE FAITH AND DEVOUTNESS FOR CONVICTS IN CLASS II B PENITENTIARY INSTITUTIONS IN INDRAMAYU - Moch Fachri Muzhaffar; Ali Muhammad (KABILAH : Journal of Social Community, 2022)
Abstract: Islamic religious guidance is expected to enable convicts to be able to develop the quality of life and life, both as individuals and as members of society, so that after leaving the Penitentiary they will have the provision of knowledge, faith and become fully human beings who can carry out a better life in society. In carrying out the research, a descriptive research method was used where the data used used population and sample data where convicts were the population in Class I Correctional Institutions in Tangerang, while the samples were prisoners who participated in Islamic religious training in Class II B Correctional Institutions in Indramayu. Then to support the research, data collection was carried out by observation, interviews, and literature studies. Finally, it can be concluded that religion is a very important need for humans, with religion humans have a way of life as a provision to face problems in their lives. With the development of the Islamic religion at Class II B Penitentiary in Indramayu, it is hoped that convicts will understand Islam, repent and practice it in daily life and be aware of mistakes that can harm society and themselves. Keywords: Development of the Religion of Islam, Private and Community